Understanding the mechanical properties of hot pressed Ba-doped S-phase SiAlON ceramics - Basu B.; Manisha; Mukhopadhyay N.K. (My University, 2025)
In this contribution, we report the analysis and interpretation of the mechanical property measurements for a new class of SiAlON ceramic. The hardness and indentation fracture toughness were measured on the hot pressed Ba-doped S-SiAlON ceramic using Vickers indentation at varying loads (up to 300 N). An important observation was that all the investigated S-SiAlON exhibited the characteristic rising R-curve behavior with a maximum toughness of up to 10-12 MPa m1/2 for ceramics, hot pressed both at 1700 and 1750 °C. Crack deflection by large elongated S-phase grains and crack bridging by β-Si3N4 needles has been found to be the major toughening mechanisms for the observed high toughness. Theoretical estimates, using a toughening model based on crack bridging and deflection by platelet shaped 'S'-phase grains and β-Si3N4 needles, reveal the interfacial friction of around 200 MPa. Careful analysis of the indentation data reveals the average (apparent) hardness modestly increases with indent load in all S-SiAlON samples, with more significant effect for S-SiAlON, hot pressed at 1600 °C. This effect has been analyzed in the light of the established model of 'indentation-induced cracking' phenomenon. Our experimental results suggest that a modest combination of average hardness of 15 GPa and indentation toughness of around 12 MPa m1/2 could be achieved in Ba-S-SiAlON ceramic and further improvement requires microstructural tailoring. © 2008 Elsevier Ltd. All rights reserved.